An Experimental Study on Structural Behavior of Lathe Waste in Conventional and Self-Compacting Concrete - Bhavana, Aluri; L. Sai Rangarao, M (International Journal of Engineering and Technology, 2018)
To diminish the effect on condition and impact of soil disintegration the lathe waste or steel scrap i.e. machine squander, which is acquired from mechanical machines, can be utilized as reusing material in the concrete blend. This project emphasizes the study on self-compacting concrete (SCC) and conventional concrete (CC) with the addition of machine squander. The investigation is done with and without the addition of steel scrap in conventional and self-compacting concrete. The optimal content of steel scrap is utilized out of 1%, 2%, and 3%. Multiple trail mixes were carried out to find out the optimal content of steel scrap. The fresh and hardened properties of concrete are resolved. The test completed determining flow properties of SCC are Slump, L-box, V-funnel tests.Â The flexural, compressive and split tensile strengths of concrete were resolved. A total 8 beam specimens were cast and tested under simply supported condition. Deformational behavior was compared between conventional concrete, beam specimens to SCC concrete beam specimens.Â Â